2020
DOI: 10.34117/bjdv6n4-131
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição das comunidades zooplanctônicas ao longo do litoral norte do Maranhão, Brasil

Abstract: Distribuição das comunidades zooplanctônicas ao longo do litoral norte do Maranhão, Brasil Distribution of the zooplanctonic communities along the north coast of Maranhão, Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…The analysis of the similarity of the São Luís and São José de Ribamar tide-control structures shows that there was homogeneity of the zooplankton, that is, regardless of the influences of the anthropic agents, such as the tidal containment structure itself, the communities are probably able to maintain equilibrium. Finally, this study found zooplanktonic groups like those of Nunes et al (2020) on the coast of Maranhão.…”
Section: Discussionsupporting
confidence: 62%
“…The analysis of the similarity of the São Luís and São José de Ribamar tide-control structures shows that there was homogeneity of the zooplankton, that is, regardless of the influences of the anthropic agents, such as the tidal containment structure itself, the communities are probably able to maintain equilibrium. Finally, this study found zooplanktonic groups like those of Nunes et al (2020) on the coast of Maranhão.…”
Section: Discussionsupporting
confidence: 62%
“…Assim, os diversos organismos que compõe a fauna desta área, os zooplanctôns estão entre os mais diversos e abundantes (Nunes et al 2020). Isto se deve ao fato de serem compostos por pequenos animais pertencentes a grandes filos, como Arthropoda, Cnidaria, Foraminifera, Chaetognatha e outros, os quais desempenham papel fundamental na ciclagem de nutrientes e na transferência de carbono no meio marinho, sendo funcionalmente considerados como elos entre produtores (fitoplâncton), e consumidores sequentes, dentro da cadeia trófica marinha (Leandro et al 2014;De-Carli et al 2017).…”
unclassified